Biomimetic peptoid oligomers as dual-action antifreeze agents - Huang, Mia L. (National Academy of Sciences, 2012)
The ability of natural peptides and proteins to influence the formation of inorganic crystalline materials has prompted the design of synthetic compounds for the regulation of crystal growth, including the freezing of water and growth of ice crystals. Despite their versatility and ease of structural modification, peptidomimetic oligomers have not yet been explored extensively as crystallization modulators. This report describes a library of synthetic N-substituted glycine peptoid oligomers that possess “dual-action” antifreeze activity as exemplified by ice crystal growth inhibition concomitant with melting temperature reduction. We investigated the structural features responsible for these phenomena and observed that peptoid antifreeze activities depend both on oligomer backbone structure and side chain chemical composition. These studies reveal the capability of peptoids to act as ice crystallization regulators, enabling the discovery of a unique and diverse family of synthetic oligomers with potential as antifreeze agents in food production and biomedicine.